A seed–seedling conflict for Atriplex polycarpa shrubs competing with exotic grasses and their residual dry matter. Issue 4 (4th April 2021) - Coleman, Mitchell L.; Mayence, C. Ellery; White, Michael D.; Jacobsen, Anna L.; Pratt, R. Brandon
Abstract: Native saltbush, Atriplex polycarpa, shrub populations are widely diminished and fragmented in the southern San Joaquin Desert of California due to habitat conversion and invasion by exotic annual grasses of mostly Mediterranean origin. The role these grasses play in saltbush population demography is not well understood. We hypothesized that saltbush seedling recruitment and growth is limited by the competitive interactions with exotic grasses, preventing saltbush stands from maintaining their populations and expanding. We predicted that saltbush seedling recruitment would be reduced by (1) light and moisture competition with the grasses; and (2) the physical barrier of grass residual dry matter (RDM) formed during senescence. To test our predictions, we investigated saltbush seedling recruitment under field conditions across six saltbush populations. We examined how variations in edaphic structure and water availability by site may have affected saltbush seedling recruitment and longer‐term population dynamics. In experimental plots where saltbush seeds were sowed, exotic grass RDM reduced saltbush seedling emergence compared to seeds sown in the absence of RDM; competition post‐emergence was not significant. Saltbush seedlings transplanted into the field had lower mortality and less herbivory in invaded grassy habitats compared to seedlings planted in bare zones in between established, mature saltbush shrubs. Edaphic variation and water availability by site were likely key factors affecting the success of both grass invasion and saltbush recruitment. Our results suggest that there is a seed–seedling conflict: Sites favorable for saltbush seedling emergence (minimal grass cover among mature shrubs) are unfavorable for seedling survival due to high herbivory. Conversely, sites favorable for saltbush seedling survival (high grass coverage away from mature shrubs) are unfavorable for seedling emergence. The RDM produced by grasses represents an important stabilizing feedback favoring continued grass dominance.